Feeding Behavior of Sweet Potato Weevil, Cylas formicarius (Fabricius) (Coleoptera Brentidae) on Three Sweet Potato, Ipomoea batatas L. Cultivars Grown in Tarlac, Philippines - Novenario, Jerah Mystica B.; Ceballo, Flor A. (2024)
Sweet potato is grown in tropical countries for its edible tubers, which have become an essential food source. It is usually propagated through vine-cutting, which can be obtained from harvested plants or nurseries intended for cutting production only. The recurrent use of vines may cause increased weevil infestation. The crop is known to be infested with insect pests. More importantly, the sweet potato weevil, Cylas formicarius, targets the tubers, thus, causing the economic losses. Sweet potato farmers in Tarlac claim that only one sweet potato cultivar is being attacked by C. formicarius, however, it was found in this experiment that the feeding and feeding behavior of the weevil were not affected by the cultivar provided, such that there is no significant differences observed in the average amount of tubers consumed by both male and female feeding time and degree of damage
Keywords: Sweet potatoes--Diseases and pests; Sweet potato weevil